2019
DOI: 10.1111/jnc.14927
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil‐induced oligodendrocyte differentiation is mediated through estrogen receptors

Abstract: Loss of oligodendrocytes, the myelin-forming cells of the central nervous system, and subsequent failure of myelin development result in serious neurological disorders such as multiple sclerosis. Using primary mouse embryonic neural stem cells (NSCs), we previously demonstrated that donepezil, an acetylcholinesterase inhibitor developed for the treatment of Alzheimer's disease, stimulates the differentiation of NSCs into oligodendrocytes and neurons, albeit at the expense of astrogenesis. However, the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…Sox-10 is a mouse monoclonal antibody specific to an epitope mapping between amino acids 2–29 at the N-terminus of the human Sox-10 gene. Sox-10 has been shown to specifically label the oligodendrocyte lineage in the CNS and in mouse brains ( Zuo et al, 2018 ; Barak et al, 2019 ; Imamura et al, 2020 ). Both primary antibodies were visualized using two fluorescent-conjugated secondary antibodies which are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Sox-10 is a mouse monoclonal antibody specific to an epitope mapping between amino acids 2–29 at the N-terminus of the human Sox-10 gene. Sox-10 has been shown to specifically label the oligodendrocyte lineage in the CNS and in mouse brains ( Zuo et al, 2018 ; Barak et al, 2019 ; Imamura et al, 2020 ). Both primary antibodies were visualized using two fluorescent-conjugated secondary antibodies which are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, several reports in the literature have focused on the ability of ChEI to induce neuronal recovery by increasing neurogenesis and neuritogenesis. Several studies demonstrated that donepezil could promote neuronal differentiation and neurite growth in vitro and in vivo [ 80–84 ]. Similar effects were also found for tacrine, galantamine, and rivastigmine [ 85–90 ].…”
Section: Neuroprotective Effect Of Traditional Che Inhibitorsmentioning
confidence: 99%
“…The efficacy of each of them has been extensively studied in several studies, both in animal models and clinical trials. Its use has shown that it has a beneficial effect in all stages of the disease and could also have a neuroprotective effect by increasing cell viability and reducing neuronal death, as well as the presence of inflammatory mediators [ 225 , 226 ].…”
Section: Therapymentioning
confidence: 99%
“…Donepezil is widely prescribed and has been considered a first-line treatment for AD since 1996 with selective activity for AChE. Several studies have indicated that the use of donepezil can reverse the clinical symptoms present in AD and has also been shown to have an anti-neurodegenerative effect, promoting neuronal differentiation and neurite growth [ 225 ]. In animal models, donepezil induced cognitive and behavioral improvements [ 230 ].…”
Section: Therapymentioning
confidence: 99%